[OA109] Validation of a radio-guided surgery technique based on beta-radiation: Test on ex-vivo specimens. (August 2018) - Camillocci, Elena Solfaroli; Mancini-Terracciano, Carlo; Bertani, Emilio; Bocci, Valerio; Colandrea, Marzia; Collamati, Francesco; Cremonesi, Marta; Ferrari, Mahila Esmeralda; Ferroli, Paolo; Ghielmetti, Francesco; Grana, Chiara Maria; Marafini, Michela; et al.
Abstract : Purpose: A very promising technique for radio-guided surgery (RGS) based on β -radiation is being developed. The lower background, with respect to the established approach with high penetrant γ radiation, can allow for a large diffusion of such a technique and extending the RGS to cases with a large uptake of surrounding healthy organs, such as abdominal and brain neoplastic disease or tumor of infancy. Methods: To validate the β -RGS feasibility study, tests on ex-vivo specimens of brain meningioma and gastro-entero-pancreatic neuroendocrine tumors have been performed. These clinical cases were selected between the tumors known to express receptors to a β -emitting radio-tracer already in use in the clinical routine: 90 Y-labelled DOTATOC. Voluntary patients were enrolled according to the standard uptake value (SUV) and the expected tumor-to-non-tumor ratios (TNR) estimated from PET/CT images after administration of 68 Ga-DOTATOC. All of them gave written informed consent to participate in the clinical trial, already approved by the Ethics Committee. After administration of a low activity (about 2.5 mCi) of 90 Y-DOTATOC, the extracted ex-vivo specimens and the healthy tissue around the lesions were examined to assess the correlation between the counting rates measured by the developed β -detecting probe and the expected 90Y activity. Results: All the neoplastic samples were correctly identified. A dependence of the counting rate both on the volume V and on the total activity of the sample were observed. Even injecting as low as 1.4 MBq/kg of radio-tracer, tumor remnants of 0.1 ml would be detectable in few seconds. Conclusions: The results of the clinical tests showed the validity of the underlying assumptions and strengthening the feasibility studies already published. Small radiopharmaceutical activity is required to detect a tumor remnant as expected due to the low background rates. The negligible medical staff exposure was also confirmed.